Investigating ministry names for comparative policy analysis: lessons from energy governance - Tosun, Jale (Journal of comparative policy analysis, 2018)
This commentary contends that ministry names offer a valuable construct for furthering the state of comparative policy analysis. Using energy governance as an example, this study shows that ministries’ names are stable in some countries but subject to changes in others. Furthermore, there is variation in the ministries’ names over time. Creating or maintaining a ministry that explicitly mentions “energy” is interpreted as signaling enhanced political attention to this issue, whereas removing the referral to “energy” signals the opposite. The names of ministries responsible for energy matters also affect energy policy outputs. Drawing on 43 OECD and BRICS countries, the empirical analysis shows that countries which have ministries in place that mention “energy” together with “economy” in their names are swifter in adopting renewable energy targets. Ministries that mention “economy” along with “climate” and/or “environment” also have an inclination to be faster in adopting such targets, but the coefficients fail to reach conventional levels of statistical significance. Given this finding, it appears worth pursuing this line of research further.